Analisis Yurisdiksi Mahkamah Pidana Internasional (ICC) Dalam Kasus Rohingya : Persepktif Hukum Internasional - Mustafa, Firman; Dewi, Mira Nila Kusuma; Jahudin, Rayindra; Akbar, Arifin; Has, A. Altin Aslam; Yusril, Muh.; S, Sunardi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the jurisdiction of the International Criminal Court (ICC) in handling cases of serious human rights violations against the Rohingya ethnic group in Myanmar. Using a normative approach and literature review, the research highlights principles of international humanitarian law and international criminal law, including the 1998 Rome Statute as the basis of ICC jurisdiction. The Rohingya case is categorized as a non-international armed conflict involving alleged serious human rights violations, including genocide, crimes against humanity, and war crimes. The study reveals that although the ICC’s complementarity principle allows the international court to act when national judicial systems are unable or unwilling to enforce the law, the exercise of ICC jurisdiction faces various obstacles, such as Myanmar’s lack of cooperation, Myanmar’s non-party status to the Rome Statute, and regional political constraints related to the ASEAN non-intervention principle. The findings indicate that despite significant challenges, the ICC still plays a strategic role in upholding international justice for the Rohingya community through the recognition of jurisdiction over violations occurring in the territory of Rome Statute states or through referrals by the United Nations Security Council.